The Reconstruction of the Nasal Columella Defect Using Domino Flaps - Linh, Le Diep; Lan, Luu Phuong; Tien, Nguyen Phuong; Manh, Nguyen Quoc; Lam, Vu Ngoc; Duc, Nguyen Quang (Archives of Plastic Surgery, 2024)
Skin defects of the total nasal columella can significantly impact both nasal respiratory function and aesthetics. The reconstruction of total columella is a complex process and represents a significant challenge for plastic surgeons. Various factors can cause the loss of the columella. Numerous columella reconstruction procedures have been proposed, each with their own set of advantages and disadvantages. The main issues to address include the need for regional flaps from the forehead or nasofacial sulcus, a long pedicle to reach the columella, and the double angular folding that causes a risk of malnutrition or venous congestion. Additionally, using horizontal nasolabial flaps may lead to deformation of the upper lip.In this study, we present a new procedure to reconstruct the nasal columella using “Domino flaps” with two flaps (the horizontal upper lip island flap and nasocheek island flap). This new procedure ensures adequate skin for reconstruction of nasal columella and partial tip, minimizes rotation angle, reduces the angular folding of the pedicle, furthermore limits deformation of the upper lip. “Domino flaps” are a valuable option for surgeons when reconstructing the total nasal columella. However, it is important to consider whether the patient has a beard at the donor sites.
Keywords: nasal columella defect; nasocheek island flap; horizontal upper lip island flap; Domino flaps